2016
DOI: 10.1016/j.ejps.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical compartment model for antigen kinetics in the skin

Abstract: The skin is a promising location for vaccination with its abundant population of antigen capturing and presenting cells. The development of new techniques, such as the use of microneedles, can facilitate the delivery of vaccines into the skin. In recent years, many different types of microneedle arrays have been designed. However, their geometry and arrangement within an array may be optimized to trigger sufficient antigen presenting cells. A computational model can support the rational design of microneedle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…In contrast, MN patches are dry formulations that slowly hydrate, form a viscous gel of sugars and polymers and eventually clear from skin, thereby lengthening antigen presentation [17,50]. The clearance rate of vaccine from the skin has been shown previously to depend on the antigen and formulation used, as well as the uptake and migration of APCs in the skin [17,18,[51][52][53].…”
Section: Microneedle Patches With Extended Deliverymentioning
confidence: 99%
“…In contrast, MN patches are dry formulations that slowly hydrate, form a viscous gel of sugars and polymers and eventually clear from skin, thereby lengthening antigen presentation [17,50]. The clearance rate of vaccine from the skin has been shown previously to depend on the antigen and formulation used, as well as the uptake and migration of APCs in the skin [17,18,[51][52][53].…”
Section: Microneedle Patches With Extended Deliverymentioning
confidence: 99%
“…For each specific situation, the relevant kinetic parameters, number of receptors and dose should be determined. In our previous study, we showed that from these parameters the number of receptors and dose had the largest influence on the output of the model (Römgens et al 2016). In the current study, the model was used to provide an insight into the efficiency of dermal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that the rate constants had little effect on the output of the model and can therefore be taken from general values from the literature (Römgens et al 2016). The initial receptor concentration was estimated from the cell density (6.2 × 10 4 cells/mm 3 for the dermis, 1.3 × 10 6 cells/mm 3 for the epidermis) and the number of receptors per cell (1 × 10 5 ) for both the epidermis and dermis (Avraméas et al 1996;McLellan et al 1998;Szolnoky et al 2001;Mulholland et al 2006;Römgens et al 2016). The diffusion coefficient in both these layers was based on measurements with 40 kDa dextran (Römgens et al 2015).…”
Section: Transport and Kinetics In The Skinmentioning
confidence: 99%
See 2 more Smart Citations